Achievement of character education in different types of elementary school - Mujahidin, Endin; Nasution, Syamsuddin Ali (Ibn Khaldun Journal of Social Science, 2019)
Elementary education is a basic level of education that will affect a person's character in the further. If children are educated by good and appropriate educational method in elementary school, they will perform as a good quality or character of person. The aim of this study was to evaluate the achievement of character education in different types of elementary school. There are three types of school observed, that is public, religion, and culture school, and two schools for each types. There were six principal characters evaluated were faithful, pious, noble, self reliant, democratic and responsible. The results showed that Islamic boarding schools and cultural based schools reinforce the character education to students more frequently than the public school. The achievement of character of students in Islamic boarding schools and cultural based schools better than that in public school, indicated by higher grading. While the characters of faith and piety in elementary schools, is generally in need very serious attention.